The Risk of Bladder Cancer in Korean Diabetic Subjects Treated with Pioglitazone - Song, Sun Ok (Korean Diabetes Association, 2012)
BACKGROUND: There is growing concern regarding the increased incidence of bladder cancer in diabetic patients using pioglitazone. This study aimed to investigate the association between bladder cancer and the use of pioglitazone in Korean diabetics. METHODS: This retrospective, matched case-control study included a case group (n=329) of diabetic patients with bladder cancer who presented at the Severance Hospital from November 2005 to June 2011. The control group consisted of patients without bladder cancer (1:2 ratio matching for sex and age, n=658) who were listed on the Severance Hospital diabetes registry. RESULTS: The percentage of subjects who had ever used pioglitazone was significantly lower in the case group than in the control group (6.4% vs. 15.0%, P<0.001). Multivariate conditional logistic analysis revealed that independent factors affecting bladder cancer were smoking (odds ratio [OR], 11.64; 95% confidence interval [CI], 6.56 to 20.66; P<0.001), coexisting cancer (OR, 6.11; 95% CI, 2.25 to 16.63; P<0.001), and hemoglobin levels (OR, 0.78; 95% CI, 0.69 to 0.88; P<0.001). The OR of the history of pioglitazone use was 2.09 and was not significantly different between the two groups (95% CI, 0.26 to 16.81; P=0.488). CONCLUSION: A relationship between pioglitazone use and incidence of bladder cancer was not observed in Korean diabetic patients. This suggests that the risk for bladder cancer in Korean diabetic subjects treated with pioglitazone might be different from that of Caucasian populations. Large-scale, well-designed and multi-center studies are needed to further evaluate this relationship.